A SANDBOX MODEL TO STUDY A CONDUCTIVE BARRIER - Guedes, Ana Claudia; Wendland, Edson Cezar (Águas Subterrâneas, 2017)
The most common disposal method of municipal solid waste (MSW) is the landfill, whi ch represents a potential source of pollution to water resources when not properly desig ned, monitored and closed. The aim of this research is to evaluate an innovative techniq ue to reduce the groundwater lateral flow inside contaminated areas to some acceptable level. The method consists in a vertical barrier of high hydraulic conductivity, called co nductive barrier, that conducts the flow inside its structure. Since an experimental study is essential before in situ applications, this work presents the sandbox model that has be en constructed to analyze the groundwater flow through a conductive barrier. The aim o f this research is to verify, in laboratory, the effectiveness of the proposed method, whic h represents an alternative to reduce groundwater contamination in countries where inad equate disposal of MSW are still an issue.